Osteogenesis imperfecta (lethal) bones contain types III and V collagens. Issue 6 (June 1980) - Pope, F M; Nicholls, A C; Eggleton, C; Narcissi, P; Hey, E N; Parkin, J M
Abstract : Lethal osteogenesis imperfecta (OI-L) and normal fetal bones contain types I and V collagen with relatively more type V in OI-L bones. The latter, unlike normal fetal bone, also contain some type III collagen. Such altered collagen ratios could directly produce the bony fragility and radiotranslucency of OI-L bones. Since this is an inherited osteoporosis similar alterations in acquired osteoporoses are also possible.